PENGARUH CITRA MEREK DAN PENETAPAN HARGA TERHADAP KEPUASAN PELANGGAN PADA BUTIK NINTYNINE FASHION HIJAB KEDIRI - Lila Megavia P; Sri Wahyuni Mega2; Lina Saptaria (CV SWA Anugrah, 2023)
This research aims to determine the influence of brand image and pricing on customer satisfaction at the Ninetynine Fashion Hijab Kediri Boutique. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to customers of the Ninetynine Fashion Hijab Kediri Boutique and calculated using the SPSS Version 25 application. The population in this study was all unlimited customers of the Ninetynine Boutique with a sample size of 384 which was calculated using the lemshow formula. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, and R2 Coefficient of Determination Test. In the Validity Test, it is known that all question items (X1, X2, and Y) have a significance value of 0.000 < 0.05 so that each variable is declared valid. Then in the Reliability Test each variable was declared reliable because it had a Cronbach's Aplha value > 0.60. Then in the t test it is known that the brand image (X1) and pricing (X2) variables have a significance value of 0.000 <0.05 so that these two variables partially have a significant effect on customer satisfaction. Then the F test shows that the significance value is 0.000 < 0.05, which shows that brand image and pricing simultaneously influence customer satisfaction at the Ninetynine Fashion Hijab Boutique Kediri.